PENINGKATAN PENGETAHUAN HUKUM MELALUI PENYULUHAN DASAR-DASAR KONTRAK BISNIS BAGI UMKM: Basics of Drafting Business Contract for MSMEs - Sharda Abrianti; Ramadhana Anindyajati Bachry (Universitas Trisakti, 2023)
Micro, small and medium enterprise (MSMEs) as business owner, in running their business also cannot rule out the role of business contract when running their business. One of the aspect that deserve attention from the perspective of MSMEs, is the legal aspect of agreements and business contract drafting techniques, so that MSMEs owners become more legal literate, and they understand the importance of a business contract as a support for securing their business, in order to avoid further potential disputes with their business partners. Basics of drafting business contract for MSMEs is important because there are still many MSMEs owner who are not yet legally literate, including understanding the importance of making written agreements with their business partner. The method that being used in this activity is in the form of descriptive legal counseling, and the question asked are answered by conducting an analysis based on regulations and the principle of contract law. The counseling on the basics of drafting business contract for MSMEs delivered to Komunitas Pebisnis Pemula Jakbar can be said to be successful, considering that from the impressions and messages conveyed by the participant, most of them stated that the material presented was very important because they had never received counseling related to contract law, and they hope that it can be continued with legal counseling activities with other materials that can support MSMEs.